The Everyday Work of The School Counsellor as Perceived by Them - Monika JUREWICZ; Agnieszka PAWLUK- SKRZYPEK (Communications of International Proceedings, 2024)
The main objective of the study was a description of the work of the school counsellor with particular reference to: institutional conditions, the institution in which he/she works and which sets the conditions for the organisation and fulfilment of the tasks facing the school counsellor, and individual conditions in terms of professional competence. For the purposes of this article, the focus is on describing institutional conditions. The research was carried out using the method of a diagnostic survey, where the technique of a questionnaire created on the SurveyLab was used. A total of 190 people took part in the study. The study revealed that in the light of the everyday life of the school, there is an apparent lack of time and space to carry out tasks related to the challenges of today, especially in the field of children and young people's mental health. The school counsellor's work is mainly "here and now" and the multiplicity of tasks to be carried out prevents him or her from taking planned action related to optimising developmental conditions and encompassing the care and upbringing of all his or her subjects.
Keywords: school counsellor; everyday working life; challenges; barriers